Further Insights Into the Interaction of Human and Animal Complement Regulator Factor H With Viable Lyme Disease Spirochetes - Mühleip, Jovana Jasmin; Lin, Yi-Pin; Kraiczy, Peter (Frontiers in Veterinary Science, 2019)
Spirochetes belonging to the Borrelia (B.) burgdorferi sensu lato (s.l.) complex differ in their ability to establish infection and to survive in diverse vertebrate hosts. Association with and adaption to various hosts most likely correlates with the spirochetes’ ability to acquire complement regulator factor H (FH) to overcome the host´s innate immune response. Here we assessed binding of serum FH from human and various animals including bovine, cat, chicken, dog, horse, mouse, rabbit, and rat to viable B. burgdorferi sensu stricto (s.s.), B. afzelii, B. garinii, B. spielmanii, B. valaisiana, and B. lusitaniae. Spirochetes ectopically producing CspA orthologs of B. burgdorferi s.s., B. afzelii, and B. spielmanii, CspZ, ErpC, and ErpP, respectively, were also investigated. Our comparative analysis using viable bacterial cells revealed a striking heterogeneity among Lyme disease spirochetes regarding their FH-binding patterns that almost mirrors the serum susceptibility of the respective borrelial genospecies. Moreover, native CspA from B. burgdorferi s.s., B. afzelii, and B. spielmanii as well as CspZ were identified as key ligands of FH from human, horse, and rat origin while ErpP appears to bind dog and mouse FH and to a lesser extent human FH. By contrast, ErpC did not bind FH from human as well as from animal origin. These findings indicate a strong restriction of distinct borrelial proteins towards binding of polymorphic FH of various vertebrate hosts.